THE GEOLOGY OF KOBATUWA SITE, RESIDENCY OF NGADA CENTRAL FLORES, EAST NUSA TENGGARA - M. Fadhlan S. Intan (Penerbit BRIN (BRIN Publishing), 2009)
The Geology of Kobatuwa Site, Residency of Ngada Central Flores, East Nusa Tenggara. Kobatuwa Site is a part of Soa Basin, which is located at the Piga village, Soa Sub-district, Ngada Regency, EastNusa TenggaraProvince. Geographically this site is situated at 8°41 'l 7,4